2014
DOI: 10.2106/jbjs.m.00534
|View full text |Cite
|
Sign up to set email alerts
|

Use of Continuous Passive Motion in the Postoperative Treatment of Intra-Articular Knee Fractures

Abstract: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…However, the immobilization versus movement debate continues. Recent studies have found that CPM offers no benefit in intraarticular fractures [4] or TKA [3] in the long-term.…”
Section: Immobilization Versus Movement: the Debate Continuesmentioning
confidence: 99%
“…However, the immobilization versus movement debate continues. Recent studies have found that CPM offers no benefit in intraarticular fractures [4] or TKA [3] in the long-term.…”
Section: Immobilization Versus Movement: the Debate Continuesmentioning
confidence: 99%
“…However, its bene ts and value remain controversial due to the disparity in practice, such as differences in clinical protocols and the type of cryotherapy application [20]. CPM is a motorized device, which passively moves the knee joint within a certain degree to accelerate motion after knee fracture [21]. But the effects of CPM remain contentious in the literature [22] and rarely used now.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason for its prevalence was extensive indications. However, excessive soft tissue dissection during surgery further impaired the already damaged soft tissue envelop, along with the concomitant vascular and neurological injuries, inevitably resulting in complications related to incision and bone union.…”
Section: Introductionmentioning
confidence: 99%